2019
DOI: 10.1038/s41598-019-55513-z
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Platform Omics Analysis for Identification of Molecular Characteristics and Therapeutic Targets of Uveal Melanoma

Abstract: Currently, there is no effective treatment for metastatic uveal melanoma (UVM). Here, we aimed to identify the mechanism involving intrinsic chemoresistance of metastatic UVM and the relevant therapeutic targets for UVM. We analyzed cohorts of 80 and 67 patients with primary UVM and skin cutaneous melanoma (SKCM), respectively, using The Cancer Genome Atlas dataset. Mutational burdens identified by whole exome sequencing were significantly lower in UVM than in SKCM patients. COSMIC mutational signature analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Several key transcription regulators (TP53, MYC, SP1, TP63, E2F1), growth factors (EGF, TGFB1, FGF2, HGF) and other key regulators including PTEN, ERBB2, ESR1, KRAS and PI3K-complex were found as key targets using this analysis. Previous studies have also reported constitutive activation of these oncogenic pathways in primary UM [34,35]. Biological functions related to metastasis including cell cycle progression, cell proliferation, invasion, movement and migration were significantly enriched in the target genes.…”
Section: Figure 3: Boxplots Showing the Distribution Of The Mirna Expmentioning
confidence: 68%
“…Several key transcription regulators (TP53, MYC, SP1, TP63, E2F1), growth factors (EGF, TGFB1, FGF2, HGF) and other key regulators including PTEN, ERBB2, ESR1, KRAS and PI3K-complex were found as key targets using this analysis. Previous studies have also reported constitutive activation of these oncogenic pathways in primary UM [34,35]. Biological functions related to metastasis including cell cycle progression, cell proliferation, invasion, movement and migration were significantly enriched in the target genes.…”
Section: Figure 3: Boxplots Showing the Distribution Of The Mirna Expmentioning
confidence: 68%
“…It is worth looking at the research on long non-coding RNA, which can also serve as a potential prognostic factor [102]. The use of Multi-Platform OMICS Analysis also seems prospective [103]. Single-cell analysis, single-cell RNA sequencing, and molecular profiling are also highly promising and interesting methods [104][105][106].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings suggest that uveal melanoma may also be associated with non-Hodgkin lymphoma. Recent studies have shown that GNAQ mutations appear repeatedly in certain types of non-Hodgkin lymphoma, and other studies have suggested that MYC alterations are associated with aggressive non-Hodgkin lymphoma or a poor prognosis of uveal melanoma [ 41 , 42 , 43 ]. In addition, both skin melanoma and uveal melanoma arise from the melanocytes derived from the neural crest, and therefore, immune perturbations may also promote tumorigenesis in uveal melanoma [ 44 ].…”
Section: Discussionmentioning
confidence: 99%